Pelvic Tilt Exercise Against Lower Back Pain For Third Trimester Pregnant Women In Rejang Lebong Regency - Kurniyati Kurniyati; Derison Marsinova Bakara (Journal of Midwifery, 2020)
Changes that occur during pregnancy may be difficult during pregnancy and during childbirth. Complications during pregnancy include back pain, low back pain, pelvic pain, and shortness of breath. One of the most common discomforts is back pain. Back pain is the most common musculoskeletal problem in pregnant women. It is estimated that 50% to 70% of pregnant women suffer from this problem. The purpose of this study was to determine the effect of pelvic tilt training on the reduction of back pain in third-trimester pregnant women in the Rejang Lebong Regency. The research variable was back pain in third-trimester pregnant women measured before and after pelvic tilt exercises. The research was conducted in May-July 2020. This type of research is Quasi-Experimental, the results of the sample calculation obtained a sample of 32 people. The statistical test used to see the reduction in back pain before and after Pelvic tilt exercise is non-parametric Wilcoxon. Results of back pain in the third trimester of pregnant women after being given pelvic tilt exercise with p <0.005. There is a difference in back pain in the third trimester of pregnant women after pelvic tilt exercises.